Analisis Dukungan Keluarga, Konsep Diri dan Regulasi Diri Dalam Meningkatkan Motivasi Belajar - Nurgiyanti, Anisa; Fahmi Johan Syah, Muhammad (Jayapangus Press, 2025)
Every individual has a need to obtain education and learning. However, in this process, a sense of enthusiasm is needed which is formed through motivation to learn. With the enthusiasm to learn, individuals can gain more interest in understanding the learning that is taught. Motivation to learn is a key factor in students' academic success. Several aspects that can influence learning motivation are family support, self-concept and self-regulation. This study aims to analyze (1) the influence of family support on learning motivation, (2) the influence of self-regulation on learning motivation, (3) self-concept on learning motivation, (4) family support on self-regulation, (5) motivation of family support on self-motivation through self-regulation as a mediating variable and (6) self-concept on self-motivation through self-regulation as a mediating variable. The population in this study were students of the Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta with a total of 110 students selected using an online survey technique. Data were collected through a questionnaire that measured family support, self-concept, self-regulation, and learning motivation. The data analysis technique was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of this study indicate that (1) self-concept has a significant effect on self-regulation. (2) family support does not have a significant effect on self-regulation (3) family support also does not influence learning motivation. However, (4) self-regulation is proven to have a positive and significant effect on student learning motivation. The conclusion of this study confirms that self-regulation plays an important role in increasing learning motivation, so strategies are needed that can help students develop self-regulation skills effectively.